De novo assembly and characterization of leaf transcriptome for the development of functional molecular markers of the extremophile multipurpose tree species Prosopis alba - Torales, Susana L.; Rivarola, Máximo; Pomponio, María F.; Gonzalez, Sergio; Acuña, Cintia V.; Fernández, Paula; Lauenstein, Diego L.; Verga, Aníbal R.; Hopp, H. Esteban; Paniego, Norma B.; Poltri, Susana N. Marcucci (BMC Genomics, 2013)
Prosopis alba (Fabaceae) is an important native tree adapted to arid and semiarid regions of north-western Argentina which is of great value as multipurpose species. Despite its importance, the genomic resources currently available for the entire Prosopis genus are still limited. Here we describe the development of a leaf transcriptome and the identification of new molecular markers that could support functional genetic studies in natural and domesticated populations of this genus.